Simile in Leila S. Chudori's Pulang and Its English Version Home: An Analysis of Translation & Meaning Preservation - Linda Rahmawati, Dwi; Sega Kendenan, Esriaty (Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the translation of similes in Pulang (2012) by Leila S. Chudori and their counterparts in Home (2015) by John H. McGlynn. Indonesian literature is increasingly exported globally, and similes play a key role in enriching imagery, emotions, and cultural nuances. However, they also pose cross-linguistic challenges due to cultural differences between the source and target languages. This study has three aims: to identify similes in Pulang, to analyze translation procedures using Newmark's (1988) framework, and to evaluate meaning preservation through reader responses. A descriptive qualitative method was applied. The population consisted of 35 similes in Pulang, and a purposive sample of explicit similes — marked by conjunctions such as seperti and like — was selected. Data were collected through close reading, identification, classification, and reader response questionnaires distributed to three respondents. Analysis used descriptive frequency-percentage calculation. The results show that the most dominant procedure was reproducing the same image (20 out of 35 similes; 57.14%). Regarding meaning preservation, 60% of similes were fully preserved, 31.43% were partially preserved, and 8.57% were not preserved. Overall, the translation successfully maintained the stylistic essence of the source text. However, cultural adaptation occasionally weakened the original nuance. It is therefore suggested that translators prioritize the original imagery to improve translation accuracy.